2016
DOI: 10.18383/j.tom.2016.00127
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Renal Urea Handling in Rats at Millimeter Resolution Using Hyperpolarized Magnetic Resonance Relaxometry

Abstract: In vivo spin spin relaxation time (T2) heterogeneity of hyperpolarized [13C,15N2]urea in the rat kidney was investigated. Selective quenching of the vascular hyperpolarized 13C signal with a macromolecular relaxation agent revealed that a long-T2 component of the [13C,15N2]urea signal originated from the renal extravascular space, thus allowing the vascular and renal filtrate contrast agent pools of the [13C,15N2]urea to be distinguished via multi-exponential analysis. The T2 response to induced diuresis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 79 publications
0
47
0
Order By: Relevance
“…Thus, alternative molecules such as creatinine, which are reabsorbed to a lesser degree, could potentially improve the hyperpolarized MR-based GFR estimation. Although, while typical GFR estimations are performed with free filtered-tracers ( 32 , 2 ), the reabsorption of urea could represent a potential advantage over existing methods by allowing simultaneous estimation of the reabsorption ( 23 , 25 , 26 , 20 , 30 , 29 , 27 ). Furthermore, it has been demonstrated that several perfusion tracers can be hyperpolarized and imaged simultaneously ( 44 ), allowing more detailed knowledge on the filtration and reabsorption by combining biomarkers with different hemodynamic profiles ( 21 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, alternative molecules such as creatinine, which are reabsorbed to a lesser degree, could potentially improve the hyperpolarized MR-based GFR estimation. Although, while typical GFR estimations are performed with free filtered-tracers ( 32 , 2 ), the reabsorption of urea could represent a potential advantage over existing methods by allowing simultaneous estimation of the reabsorption ( 23 , 25 , 26 , 20 , 30 , 29 , 27 ). Furthermore, it has been demonstrated that several perfusion tracers can be hyperpolarized and imaged simultaneously ( 44 ), allowing more detailed knowledge on the filtration and reabsorption by combining biomarkers with different hemodynamic profiles ( 21 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urine concentration is directly determined by GFR, and thus, the intrarenal dependency of urea distribution in conjunction with renal function has previously been investigated in rodents and in porcine models with hyperpolarized 13 C-urea. This enables assessments of perfusion, osmolality gradients, and relaxation alterations under various functional and disease conditions ( 20 , 23 , 25 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…A potential limitation of the 13 C-acetate interpretation was the relaxation decay, which is fast and difficult to measure in vivo because the different cellular compartments exhibit variations in relaxation properties 44 . Furthermore, intra-renal 13 C relaxation differences have been demonstrated in the rodent kidney, both intra-voxel and across the kidney, indicating further improvements in the quantification by adequately accounting for these intra-renal relaxation differences 9 , 17 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 98%
“…The distribution of T 2 ’s will help sequence development and optimization, as well as analysis, as more and more compounds are developed and translated into humans. Quantitative T 2 mapping has already been performed with HP 13 C compounds [21], and can be readily translated to clinical exams, especially with the LLR+S reconstruction since larger FOVs would be required. Second, we believe the 3D dynamic acquisition can be readily translated into humans for acquisitions featuring the compounds used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced steady-state free precession (bSSFP) supports high resolution acquisitions by exploiting the long T 2 ’s of 13 C substrates, but may be especially affected by early depletion of the HP magnetization due to the high number of RF pulses required to achieve high resolution volume imaging [1418]. While bSSFP does provide the highest SNR per unit time [19] and has been used for 2D HP 13 C T 2 mapping and 3D single time-point acquisitions [14,20,21], it has not been readily applied to 3D dynamic HP 13 C acquisitions [15], especially at clinical field strengths, because of the aforementioned tradeoff in spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%